Executive Information System Modelling to Monitor Indonesian Criminal Rate - Josef Bernadi; Suharjito Suharjito (CommIT (Communication and Information Technology) Journal, 2016)
Similar to any other governments, Indonesia government has the role of protecting the security of its citizens via the established police unit. However, the executive unit is often unable to provide response in timely manner due to the huge data size. For the reason, an executive information system (EIS) is established in order to provide necessary information to leverage the decision making process. This work intends to establish and evaluate the executive information system and its support to facilitate the efforts to fight crimes in Indonesia territory. The EIS prototype is established and is evaluated on the basis of the six information system success factors where the required data are collected by means of questionnaire. The results suggest that the factors of system quality, information quality, easy-of-use, user satisfaction, and individual and organization impacts are very significant.